The Effectiveness of the Picture and Picture Learning Model to Improve the Teeth Brushing Ability of Intellectual Disability - Durrotul Lum'ah; Mohammad Efendi; Dimas Arif Dewantara (Jurnal ORTOPEDAGOGIA, 2020)
This study aims to describe the influence of the use of picture and picture learning models on the ability to attend (brushing teeth) for Class 3 SDLB C This study uses quasi-experimental research methods (quasi experiment) a form of Time Series Design. The analysis technique used is hypothesis testing using the Wilcoxon test. The results of the data analysis show that the average learning outcomes of students of ten people are five people whose values are below the class average, it can be concluded that the picture and picture learning model can improve the ability of self-brushing teeth to brush third grade students of SDLB C